Applications and translational research advances of degradable implantable hydrogels - Wang Qimeng; Yu Lisha; Mao Zhengwei (生物医学转化)
Degradable implantable hydrogels have become a research hotspot in various fields, including wound sealing, hemostasis, tissue regeneration, smart biosensors, and drug delivery systems. This is attributed to their ability to degrade and absorb in a controlled manner after achieving their intended in vivo effects, thereby avoiding the risks associated with long-term implantation and secondary surgeries. However, although extensive fundamental research has been conducted on degradable implantable hydrogels, successful cases of clinical translation remain relatively rare. This review systematically summarizes and analyzes the research advances in degradable implantable hydrogels. It focuses on the structures and types of hydrogels, advances in clinical research, and examples of translational applications. Furthermore, it discusses translational pathways in clinical applications and market potential of these materials. This review aims to provide valuable insights and references for promoting the clinical translation of degradable implantable hydrogels, thereby contributing to the development of this field.